Domestic credit growth and international capital flows - Philip R. Lane; Peter McQuade (European Central Bank (ECB), 2013)
Europe experienced substantial cross-country variation in domestic credit growth and cross border capital flows during the pre-crisis period. We investigate the inter-relations between domestic credit growth and international capital flows over 1993-2008, with a special focus on the 2003-2008 boom period. We establish that domestic credit growth in European countries is strongly related to net debt inflows but not to net equity inflows. This pattern also holds for an extended sample of 54 advanced and emerging economies.
Keywords: E51; F32; G15; 330; financial globalisation; financial stability; macro-prudential regulation